Stomach content analysis of young Russell’s oarfish (Regalecus russelii) from Taiwan, and a report on an unusual case of predation - Huang, Shih-Pin; Shao, Kwang-Tsao (Zootaxa, 2022)
In this study, we analyzed the stomach content of two individuals of rare, young Russell’s oarfish, Regalecus russelii, from Taiwan. One of them was captured alive along with larval fish and crustaceans by a stow net from the shallow waters (15-18m deep) of the Tamsui River mouth. A total of 38 individuals of larval fish belonging to three species (86.4% of all prey) and 6 individuals of crustaceans belonging to three species were found in the Russell’s oarfish specimen’s stomach. Among the prey, the Japanese anchovy (Engraulis japonicus) was the most dominant fish species, accounting for 44.7% of all fishes; and luciferids were the most dominant crustaceans, accounting for 66.7% of all crustaceans. All the prey fish were sandy or a mixture of sandy and muddy sediment dwellers. The luciferids and Japanese anchovies are characterized by having diel vertical migration behavior. Based on the sampling information and biological characteristics of the fish larvae and crustaceans, we conjectured that the abundance of these prey when they moved up to the upper layer of the Tamsui River mouth at nighttime had attracted the young Russell’s oarfish to hunt there. In addition, we speculated that it might be easier for the vertical-swimming Russell’s oarfish to hunt a large number of luciferids assembled in the upper layer of the water by its particular posture or angle of view.